Exploring the Potential of E-Government in Reducing Corruption – Case of Egypt - Abou ElSeoud, Mahinour (AUC Knowledge Fountain, 2024)
Many countries have recognized the significance of electronic work transition to application, frequently known as e-government, with the purpose of improving their bureaucratic performance and reducing corruption. From an economic standpoint, transparency may boost government efficiency as it increases the government capacity and, eventually, fosters good governance by reducing corruption and inefficiency. As a result, this study aims to analyze the correlation between e-government and corruption, as well as whether e-government reduced the detrimental effects of corruption on public trust. To accomplish this objective, the thesis focuses on in-depth interviews with citizens of all ages, socioeconomic and educational backgrounds, as well as policy experts and scholars. The study's findings reveal that respondents recognize the importance of the e-portal in helping them save time, effort, and even money when completing any official form. This, however, applies only to people who are technologically literate. People with no access to the internet or even a basic comprehension of this digital tool, on the other hand, are unable to use the e-portal and consider it a burden.